2016
DOI: 10.1002/2016jc012018
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling estimates of the ratio of heat and salt fluxes at the ice-ocean interface

Abstract: The heat exchange between floating ice and the underlying ocean is determined by the interplay of diffusive fluxes directly at the ice–ocean interface and turbulent fluxes away from it. In this study, we examine this interplay through direct numerical simulations of free convection. Our results show that an estimation of the interface flux ratio based on direct measurements of the turbulent fluxes can be difficult because the flux ratio varies with depth. As an alternative, we present a consistent evaluation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…Capturing three-dimensional topographical features, such as scallops, which do affect momentum and heat transfers (Bushuk et al. 2019), in coupled fluid–solid simulations would be a major achievement, which could complement fluid-only simulations at planar ice boundaries (Gayen, Griffiths & Kerr 2016; Keitzl, Mellado & Notz 2016 a , b ; Mondal et al. 2019; Vreugdenhil & Taylor 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Capturing three-dimensional topographical features, such as scallops, which do affect momentum and heat transfers (Bushuk et al. 2019), in coupled fluid–solid simulations would be a major achievement, which could complement fluid-only simulations at planar ice boundaries (Gayen, Griffiths & Kerr 2016; Keitzl, Mellado & Notz 2016 a , b ; Mondal et al. 2019; Vreugdenhil & Taylor 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the diffusive layer (further away from the ice interface), fluxes are usually dominated by turbulent processes in the outer layer which has a thickness in the order of 10 m. The turbulence is due to a combination of natural convection from buoyant melt water, strong shear ambient flows, internal waves, and ocean tides (Cenedese & Gatto, 2016; Gayen et al, 2016; Keitzl et al, 2016). Next to the ice face, meltwater is positively buoyant compared to the ambient seawater and forms a convective plume.…”
Section: Ice‐ocean‐atmosphere Interactionsmentioning
confidence: 99%
“…In the Martin and Kauffman (1977) experiments the density was dominated by the cooled temperature profile beneath the salt boundary layer, causing a peak in density that triggered convection. The velocity field was not examined in these experiments, however a numerical study of a melting boundary was conducted by Keitzl et al (2016), where similar convection was observed. The Keitzl et al (2016) simulations showed convective plumes descending from a region immediately below the salt boundary layer, although here the far-field temperatures were larger, varying between 10 • C and 24 • C. Martin and Kauffman (1977) did not observe staircase formation, however their experimental set-up had no ambient stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity field was not examined in these experiments, however a numerical study of a melting boundary was conducted by Keitzl et al (2016), where similar convection was observed. The Keitzl et al (2016) simulations showed convective plumes descending from a region immediately below the salt boundary layer, although here the far-field temperatures were larger, varying between 10 • C and 24 • C. Martin and Kauffman (1977) did not observe staircase formation, however their experimental set-up had no ambient stratification. Turner (1968) observed the progressive formation of staircases when heating a stable salt stratification from below, suggesting staircases may form in a stable stratification when double-diffusive convection is forced by a destabilising flux at the boundary.…”
Section: Introductionmentioning
confidence: 99%